Backscattered electron images, X-ray maps and Monte Carlo simulations applied to the study of plagioclase composition in volcanic rocks - Galván Josa, Víctor Martín (2013)
Zoning patterns in plagioclases are related to abrupt changes in the anorthite content along the crystal growing direction. Accurate characterization of these patterns by electron microprobe is useful to identify magma chamber processes such as recharge, mingling and whole-chamber overturn events. In this work, a new procedure to obtain high resolution quantitative maps of anorthite concentration in single plagioclase crystals is developed. The methodology consists of performing a calibration of backscattered electron images using quantitative X-ray maps. The ultimate resolution of characteristic X-rays and backscattered electron signals is studied by Monte Carlo simulation. The method is applied to characterize the chemical composition of a volcanic plagioclase from the Cerro Vilama, Argentina. The results obtained are more precise than the values given by the methods commonly used in the study of plagioclase composition, i.e. the classical profiling by electron microprobe point analysis or the modern backscattered electron image calibration by means of quantitative energy or wavelength dispersive X-ray analysis at a few selected points. © 2012 Elsevier B.V. All rights reserved.